2019
DOI: 10.1039/c9se00689c
|View full text |Cite
|
Sign up to set email alerts
|

Grid-scale energy storage with net-zero emissions: comparing the options

Abstract: Carbon-neutral energy storage will be an essential technology in delivering a decarbonised, resilient energy system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…83 Because a DAC facility can provide on-site CO 2 generation anywhere, its application is advantageous in addition to its environmental benefits. Recently, the potential application of adsorption-based DAC in indoor air removal, 115,191,193,208,209 CO 2 fertilization, 178,210 biomass production, [211][212][213][214][215] fuel production (CH 4 , 68,70,75,[216][217][218][219][220][221][222] methanol, 71,[223][224][225][226] aviation fuel, 73,[227][228][229][230][231][232] hydrocarbons 233 ), chemicals (Fischer-Tropsch process, 234,235 carbon nanotubes, 236 dimethyl carbonate, 237 syngas 238,239 ), mineralization, [240][241][242][243][244] storage, 245,246 enhanced oil recovery (EOR), …”
Section: Overview Of Adsorption-based Dac Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…83 Because a DAC facility can provide on-site CO 2 generation anywhere, its application is advantageous in addition to its environmental benefits. Recently, the potential application of adsorption-based DAC in indoor air removal, 115,191,193,208,209 CO 2 fertilization, 178,210 biomass production, [211][212][213][214][215] fuel production (CH 4 , 68,70,75,[216][217][218][219][220][221][222] methanol, 71,[223][224][225][226] aviation fuel, 73,[227][228][229][230][231][232] hydrocarbons 233 ), chemicals (Fischer-Tropsch process, 234,235 carbon nanotubes, 236 dimethyl carbonate, 237 syngas 238,239 ), mineralization, [240][241][242][243][244] storage, 245,246 enhanced oil recovery (EOR), …”
Section: Overview Of Adsorption-based Dac Technologiesmentioning
confidence: 99%
“…In general, DAC and electrolyzer costs account for a large portion of the overall production costs and determine the overall energy efficiencies. 71,217,220,226,230 Emphasis was also given to the cost of using different renewable energies and the inflexibility of processes, such as DAC, water desalination, and fuel synthesis. Berger et al 219 studied methane production in North Africa using a combination of solar and wind energy as well as its delivery to northwestern European markets.…”
Section: Reported Amentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential for expansion is inherently limited; there is an insufficient amount to balance inter-seasonal variations (Geth et al, 2015), leading to a search for alternatives, such as chemical storage in the guise of so-called "power-to-x". However, when chemical storage is discussed, this tends to be limited to hydrogen (Akinyele and Rayudu, 2014;Beaudin et al, 2010;Chen et al, 2009;Díaz-González et al, 2012;Mahlia et al, 2014), despite there being limited evidence that it is the most cost-effective option (Yao et al, 2019). Research efforts in this space have, thus far, focused on the techno-economics of standalone power-to-gas systems in Germany, possibly due to the focus of the Energiewende on the expansion of renewable energy generation (Glenk and Reichelstein, 2019;Götz et al, 2016;Schiebahn et al, 2015;Varone and Ferrari, 2015).…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…On the basis of minimizing system economic costs and carbon emissions, the contribution of pollutant concentration is used as one of the optimization goals. G. Yao et al 22 studied the technical and economic feasibility of carbon capture technology for achieving carbon neutrality. By comparing carbon emission configurations under 9 different conditions at the same time, it is found that the system using carbon capture technology and combined with energy storage equipment has the highest economic and environmental benefits.…”
Section: Introductionmentioning
confidence: 99%